Muscle- and skeletal-related side-effects of statins: tip of the iceberg?. (29th August 2020) - Auer, Johann; Sinzinger, Helmut; Franklin, Barry; Berent, Robert
Abstract: The clinical spectrum of muscle- and skeletal-related side-effects of statins includes varied myalgias and weakness, an asymptomatic increase in the concentration of creatine kinase and other biochemical parameters, myositis and rhabdomyolysis. Currently, there is no consensus on the definition of 'statin myopathy'. Evidence suggests that deleterious effects may also be associated with the volume or dosage of structured exercise and/or the intensity of physical activity. Moreover, non-muscle adverse effects on the joints and tendons are often overlooked and underemphasized. The incidence of myopathy associated with statin treatment typically ranges between 1.5% and 10%. Few data are available regarding the prevalence of muscle- related symptoms associated with different statins and the distribution of affected muscles. Furthermore, discrepancies between clinical trials and daily practice may emanate, in part, because of inconsistent definitions or exclusion criteria. The pathophysiology of statin-related myopathy is incompletely understood. A dose-dependent and proapoptotic effect, direct effects on mitochondria, drug interactions and genetic factors, or combinations thereof, may be involved. Recently, a rare immune-mediated myopathy triggered by statin use has been described. With the increasing number of patients treated with statins and with more patients being prescribed high doses of potent statins to achieve low-density lipoprotein targets, muscle-related side-effects will become more prevalent. Currently, the only effective treatment is the discontinuation of statin use. Further research is needed to develop alternative LDL-lowering drugs when statins are not well tolerated and to establish additional effective strategies to manage lipids and lipoproteins.